i=0 (Information has no intrinsic meaning) - F.J. Miller (Information Research: An International Electronic Journal)
This paper was written mainly to help identify some contradictions that can be found in the notion of knowledge management though its application is wider-ranging. The author suggests that knowledge - that is to say 'what we know' - can scarcely be understood and managed even by ourselves, much less by means of sophisticated information and communications (ie groupware and shareware) technologies. We have progressed from the industrial age through the information age into what is being promoted as the 'golden age' of knowledge and, in the process, we've been led to believe that information contains meaning - rather than just standing for, provoking or evoking meaning in others. The paper argues that unless we take the trouble to face and understand the significance and implications of i=0 (ie that information has no intrinsic meaning) and that knowledge is the uniquely human capability of making meaning from information - ideally in face-to-face relationships with other human beings - we may never emerge into any 'golden' age at all! The consequences of i=0 for communications, learning, safety, quality, management (itself), and winning work are also discussed.